SREBP-1c and lipogenesis in the liver: an update1 - Ferré, Pascal; Phan, Franck; Foufelle, Fabienne (Biochemical journal, 2021)
Sterol Regulatory Element Binding Protein-1c is a transcription factor that controls the synthesis of lipids from glucose in the liver, a process which is of utmost importance for the storage of energy. Discovered in the early nineties by B. Spiegelman and by M. Brown and J. Goldstein, it has generated more than 5000 studies in order to elucidate its mechanism of activation and its role in physiology and pathology. Synthetized as a precursor found in the membranes of the endoplasmic reticulum, it has to be exported to the Golgi and cleaved by a mechanism called regulated intramembrane proteolysis. We reviewed in 2002 its main characteristics, its activation process and its role in the regulation of hepatic glycolytic and lipogenic genes. We particularly emphasized that Sterol Regulatory Element Binding Protein-1c is the mediator of insulin effects on these genes. In the present review, we would like to update these informations and focus on the response to insulin and to another actor in Sterol Regulatory Element Binding Protein-1c activation, the endoplasmic reticulum stress.Sterol Regulatory Element Binding Protein-1c is a transcription factor that controls the synthesis of lipids from glucose in the liver, a process which is of utmost importance for the storage of energy. Discovered in the early nineties by B. Spiegelman and by M. Brown and J. Goldstein, it has generated more than 5000 studies in order to elucidate its mechanism of activation and its role in physiology and pathology. Synthetized as a precursor found in the membranes of the endoplasmic reticulum, it has to be exported to the Golgi and cleaved by a mechanism called regulated intramembrane proteolysis. We reviewed in 2002 its main characteristics, its activation process and its role in the regulation of hepatic glycolytic and lipogenic genes. We particularly emphasized that Sterol Regulatory Element Binding Protein-1c is the mediator of insulin effects on these genes. In the present review, we would like to update these informations and focus on the response to insulin and to another actor in Sterol Regulatory Element Binding Protein-1c activation, the endoplasmic reticulum stress.